Efficient synthesis and antioxidant activity of novel N-propargyl tetrahydroquinoline derivatives through the cationic Povarov reaction. Issue 8 (August 2019) - Rodriguez Núñez, Yeray A.; Norambuena, Maximiliano; Romero Bohorquez, Arnold R.; Morales-Bayuelo, Alejandro; Gutíerrez, Margarita
Abstract: New N-propargyl tetrahydroquinolines6a-g have been synthesized efficiently through the cationic Povarov reaction (a domino Mannich/Friedel-Crafts reaction), catalyzed by Indium (III) chloride (InCl3 ), from the corresponding N -propargylanilines preformed, formaldehyde and N -vinylformamide, with good to moderate yields. All tetrahydroquinoline derivatives obtained were evaluated in vitro as free radical scavengers. Results showed that compound6c presents a potent antioxidant effect compared with ascorbic acid, used as a reference compound. ADME predictions also revealed favorable pharmacokinetic parameters for the synthesized compounds, which warrant their suitability as potentials antioxidant. Additionally, a theoretical study using Molecular Quantum Similarity and reactivity indices were developed to discriminate different reactive sites in the new molecules in which the oxidative process occurs.